Implementasi Undang-Undang Keterbukaan Informasi Publik dalam Upaya Mewujudkan Good Governance ( Kajian Tiga Badan Publik : Bappeda, DPKAD dan Dinas Pendidikan Kota Semarang ) - Rizki Dwi Prabowo; Dzunuwanus Ghulam Manar; Suwanto Adhi (Journal of Politic and Government Studies, 2014)
ABSTRACTThis Research was done with background that making of Public InformationOpenness Rights (UU KIP) was one of efforts to grant citizen’s rights on public informationand to optimize control of public to government thatalso encouraging Good Governance.Based on the reason the implementation of UU KIP need to be optimized in order to createtransparent, accountable, and participatory government as principals of Good Governance.On the Semarang City Government, the implementation of UU KIP has not yet runoptimaly. Because of that, in this research will reviewing many problems related to theimplementation of UU KIP, perceived problems, and supporting factors on DPKAD,Bappeda and Dinas Pendidikan KotaSemarang as SKPD whose have strategic and centralroles on development planning, budgeting, and education.This research was using qualitative research methodology refers on analyticdescriptive research. The subjects of this research were any involved groups on theimplementation of UU KIP on Bappeda, DPKAD, and Dinas Pendidikan Kota Semarang.Data collections through observations, interviews, documentations, literature studies, andthen analyzed through data reduction technique, data presentation, and verification/concluding.The Result of this research suggest that implementation of UU KIP and itssubordinate regulations, technically have not run effectively. Dinas Pendidikan is the mostready and perfect SKPD to implement UU KIP compared to Bappeda and DPKAD. Manyobstacles faced on implementation of UU KIP and its subordinate regulations were lack ofsocialization by public relation, in appropriate delegation on socialization, lack ofunderstanding on implementation of regulation by related officers, limitedness of personneland budget, and low level of participation and people’s understanding on UU KIP.To support the succeed of implementation of UU KIP were needed many factors, itwere optimized socialization so related officers get complete comprehension aboutregulation, personel and budget adjustment, and people’s understanding on UU KIP. Thusrecommendations of this research were importance of reviewing on local regulation relatedto public information openness, more detailed and comprehensive ruling regulations onoperational of UU KIP as District Regulation and people’s comprehension andconsciousness on UU KIP and the rights of public information need to be pushed and raised.Keywords: implementation, public information openness, good governance